Case report: A case of type 1 diabetes with diabetic ketoacidosis induced by envafolimab treatment in hepatocellular carcinoma - Li, Youjia; Qu, Kai; Li, Xiuli; Yang, Xin; Zhang, Kanghuai; Xie, Jiao (Frontiers in Immunology, 2025)
This case report presents a 57-year-old male with hepatocellular carcinoma who developed Type 1 Diabetes Mellitus (T1DM) and diabetic ketoacidosis (DKA) following treatment with Envafolimab, a PD-L1 immune checkpoint inhibitor. The patient experienced a rapid onset of hyperglycemia and DKA after several cycles of Envafolimab, consistent with the pattern of diabetes induced by immune checkpoint inhibitors (ICIs). Notably, the absence of diabetes-related autoantibodies suggests that the diabetes was induced by the immune-modulating effects of Envafolimab rather than a pre-existing autoimmune condition. Management required intensive insulin therapy and a multidisciplinary approach to stabilize the patient’s health. This case underscores the critical need for heightened clinical awareness and early intervention in managing severe immune-related adverse events (irAEs) associated with novel ICIs like Envafolimab. The complexity of autoimmune-related adverse events, such as the negative autoimmune profiles observed in our patient, emphasizes the importance of multidisciplinary collaboration to optimize patient outcomes. We advocate for the establishment of long-term follow-up plans, including regular monitoring for potential irAEs and endocrine function assessments, to address the chronicity of conditions post-ICI treatment. Recognizing the limitations of current understanding, there is a clear call for further research, particularly on identifying biomarkers that may predict adverse reactions to immunotherapy, to guide precision medicine and improve patient safety.